Reversible redox reactions in metal-supported porphyrin: the role of spin and oxidation state. Issue 37 (4th August 2021) - Cojocariu, Iulia; Carlotto, Silvia; Zamborlini, Giovanni; Jugovac, Matteo; Schio, Luca; Floreano, Luca; Casarin, Maurizio; Feyer, Vitaliy; Schneider, Claus Michael
Abstract : The reduced Co(i ) metal ion in the molecular array facilitates the formation of the cobalt–ligand chemical bond already at RT. We demonstrate that molecular reactivity goes beyond the sole presence of unpaired electrons in the valence shell. Abstract : On-surface molecular functionalization paved the way for the stabilization of chelated ions in different oxidation and spin states, allowing for the fine control of catalytic and magnetic properties of metalorganic networks. Considering two model systems, a reduced Co(i ) and an open-shell Co(ii ) metal-supported 2D molecular array, we investigate the interplay between the low valence oxidation and unpaired spin state in the molecular reactivity. We show that the redox reaction taking place at the cobalt tetraphenylporphyrin/Cu(100) interface, stabilizing the low-spin Co(i ) state with no unpaired electrons in its valence shell, plays a pivotal role in changing the reactivity. This goes beyond the sole presence of unpaired electrons in the valence state of the Co(ii ) metal–organic species, often designated as being responsible for the reactivity towards small molecules like NO and NO2 . The reversible Co–NO2 interaction, established with the Co(i ) leads to the stabilization of the Co(iii ) oxidation state.